Reference flipped-differential chaos ‎shift keying scheme for chaos- based ‎communications - N. Albassam, Nizar (International Journal of Engineering and Technology, 2015)
In this paper, a new differential coherent chaos-based communication system is proposed and named Reference Flipped-DCSK (RF-DCSK). By utilizing the low correlation value between a chaotic segment and its flipped version, each transmitted signal will be the sum of the information bearing signal and the mirrored version of the reference signal. This enhances the bandwidth efficiency of DCSK by doubling bits rate. Additionally, noise performance is improved at typical values of the spreading factor. According to Gaussian approximation method, theoretical expression for Bit-Error-Rate (BER) is derived. The proposed scheme is simulated and compared with Differential Chaos Shift Keying (DCSK), Correlation Delay Shift Key (CDSK) and High Efficiency -Differential Chaos Shift Keying (HE-DCSK) schemes in Additive White Gaussian Noise (AWGN) environment. Effect of spreading factor is studied. Results show that the proposed scheme clearly outperforms other systems.